„Beka z nienormalsów”, czyli satyryczny obraz niepełnosprawnych w kulturze masowej - Grzybowski, Przemysław Paweł (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2014)
In most societies disabled people are subject to taboo, in terms of laughing at their weaknesses, failures, inadequacies and differnt situations connected with their disability. However, they are becoming a more frequent ligtsome topic of different forms in mass culture (from television to the Internet) – interesting especially when they laugh at themselves. The article deals with the situations of laughing at Other in this context together with the examples of films, shows and educational projects.